Dr. Edwin Wright Letters: George Cooke - (Author); (Interviewer); (Publisher) (1960)
Notes - Mr. George Cooke writes of life in Athabasca Landing before the automobile arrived. Businesses, freighting, the fur trade and numerous settlers are mentioned by name (2 pages)